Pengaruh Kesadaran Merek, Persepsi Kualitas Dan Asosiasi Merek Terhadap Keputusan Pembelian Produk Eiger (Studi Kasus Pada Penggiat Alam Bebas di Kota Surabaya) - Pratiwi, Nadila Duwi (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2023)
This reseach aims to asses the influence of brand awareness, perceived quality and brand association to purchase decision for eiger products to outdoor activists in Surabaya. The reseach approach used is quantitative descriptive approach. The population in this reseach are outdoor activists who are members of Mapala Kawaru and Mahapala UPN totaling 886 people. The sampling technique used purposive sampling method with a total sample of 90 people. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the research hypothesis is multiple regression. The results of this reseach indicate that the variables of brand awareness, perceived quality, and brand associations have a significant simultaneous effect on the purchasing decisions. Partially, brand awareness and brand association variables have significant effect on the purchasing decisions. While the perceived quality variable has no significant effect on purchasing decisions. The results of this reseach stated that brand association is the most dominant variable.